Overcoming barriers to inclusion in education in India: A scoping review. Issue 1 (2022) - Gale, Lindsey; Bhushan, Pranashree; Eidnani, Shweta; Graham, Lorraine; Harrison, Matthew; McKay-Brown, Lisa; Pande, Rucha; Shreeraman, Shreya; Sivashunmugam, Chandhni
Abstract: Purpose: To identify successful interventions supporting teachers and school leaders to achieve inclusive education in India, including clarifying the underpinning causal logic and identifying research gaps. Methods: Indian and Australian researchers collaborated to complete a scoping review that drew together the full range of evidence of successful educational interventions related to school leadership and teaching functions, including from grey literature sources. The scoping review protocol from the Joanna Briggs Institute was followed which involved an initial statement of the search strategy, multiple rounds of processing, and thematic analysis of results. Results: Interventions contributing to a) engaging and mobilising school leaders and teachers, b) training, resourcing and supporting them, and c) monitoring and evaluating them were tabled and analysed, allowing for an analysis of which interventions had been shown to be effective. Conclusions: Findings underlined the central steppingstone in the causal logic of effective school leadership and classroom teaching and, additionally, the importance of adopting an appreciative, asset-based and collaborative approach to all work with teachers and school leaders. These findings have direct implications for all capacity-building with school leadership and teaching staff, including initial teacher training, continuing professional development, and establishing optimal network and collaborative arrangements. Graphical abstract: What are the successful interventions in India supporting teachers and school leaders to improve inclusive education in schools and classroom learning?